Highly mobile interfaces in shape memory alloys - Seiner Hanuš (MATEC Web of Conferences, 2015)
Macro-twin interfaces in single crystals of 10 M modulated Ni-Mn-Ga martensite have recently attracted a lot of attention due to the extraordinarily low twinning stress required to set them into motion; depending on the particular twinning mode, this stress can range between 0.05 and 1 MPa, and can be either strongly temperature dependent, or nearly temperature independent. The understanding to these effects is still not satisfactory, mainly due to the high complexity of these interfaces at the micro-scale (higher-order lamination) as well as at the atomistic scale (modulations of martensite). This paper brings a brief review of the recent experimental and theoretical achievements related to these highly mobile interfaces. The uniqueness of the behavior of 10 M martensite is shown by its comparison with other shape memory alloys with relatively low twinning stresses; then, this behavior is discussed in terms of its temperature dependence, strain rate dependence and the effect of the micromorphology of the interfaces.